History of sorghum breeding and seed production in the ARC “Donskoy” - V. V. Kovtunov; N. A. Kovtunova (Зерновое хозяйство России)
The current paper has presented brief information about the establishment of a sorghum breeding and seed production school at the Federal State Budgetary Scientific Institution “Agricultural Research Center “Donskoy” (formerly the State Scientific Institution All-Russian Research Institute of Grain Crops named after I.G. Kalinenko, as well as the All-Russian Research Institute of Sorghum). A great contribution to the development of the breeding program for this crop was made by famous breeders Ya.I. Isakov, B.N. Malinovsky, N.A. Shepel. Under their leadership, there was identified and developed a significant number of varieties and hybrids of grain, sweet, grass and broom sorghum. Their experience given to subsequent breeders made it possible to develop present sorghum varieties and hybrids, which are currently included in the State List of Breeding Achievements approved for use in the Russian Federation and are widely used in agricultural production. Thus, since 2021, new highly productive varieties of sweet sorghum ‘Yuzhnoye’ and ‘Feniks’ have been included in the State List. Since 2023, there have been included the white grained sorghum variety ‘Esaul’ and the sorghum-Sudan hybrid ‘Dobrynya’. There have been developed and are currently undergoing the state variety testing the grain sorghum variety ‘Sotnik’ and the Sudan grass ‘Kudesnitsa’, the sorghumSudan hybrid ‘Gordey’, the sweet sorghum variety ‘Orfey’ and the hybrid ‘Duet’.